Qigong Sensory Training Pilot Study: A Tactile Home Program for Children with or At-Risk for Autism - Tal-Atzili, Orit; Salls, Joyce (Journal of occupational therapy, schools & early intervention, 2017)
This pilot study investigated the efficacy of Qigong Sensory Training, a parent-implemented tactile intervention, in improving sensory processing and self-regulation in children with or at-risk for autism who were enrolled in early intervention. A pretest-posttest, single-subject design was implemented with three families. After 5 months, atypical sensory processing and self-regulation improved by more than one standard deviation for all children. Parenting stress decreased by more than one standard deviation for two of the mothers. These results suggest that Qigong Sensory Training can be effective for children with or at-risk for autism when provided through a coaching model in an early intervention setting.